DIGITALLY PROGRAMMABLE MULTI-SCROLL CHAOS GENERATOR ON FPGA - Karakaya, Barış; Çulcu, Fatma; Türk, Mustafa (My University, 2020)
Multi-scroll chaotic attractors exhibit higher unpredictability than doublescroll attractors. However, the more number of scrolls cost the more usage of sources. To overcome this problem, the attractor design should be simplified. This paper presents a systematic approach that enables to realize digital piece wise linear (PWL) function in nonlinear dynamical system and to obtain whole behaviors in only one model. The proposed design requires only number of scroll as input and can realize chaotic PWL signal with a fewer number of FPGA resources. In the implementation stage of the study, the discrete mathematical equations of the chaotic attractor is modelled in Xilinx System Generator (XSG) platform and realized by using Xilinx Kintex-7 KC705 Evaluation Board.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği; Bilgisayar Bilimleri; Donanım ve Mimari; Bilgisayar Bilimleri; Teori ve Metotlar; Bilgisayar Bilimleri; Yapay Zeka